Task Force for Business and Stability Operations Lessons from Afghanistan - Zimmerman, S. Rebecca (RAND Corporation, 2016)
The Task Force for Business and Stability Operations, a multi-year endeavor for the U.S. Department of Defense, sought to use private-sector strategies to create sustainable economies in Iraq and Afghanistan. In this report, RAND researchers use semistructured interviews and both public and internal documentation to identify lessons from the Task Force's activities in Afghanistan, offering insights for similar projects in the future.